Affirmative Action: Studi Tentang Keterlibatan Perempuan Dalam Partai Golongan Karya di Kabupaten Magetan - Fernandez, Frederik; Darsono, Darsono; Sulistyani, Utami (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2022)
This study aims to describe the principles of justice applied to women in political activities. It also describes the process of cadre of women to be actively involved in political activities through leadership training. Also observe deeply the partiality of women in institutional affirmative action. Describe the various concrete experiences experienced by women in their political activities and what the party has done in preparing female cadres in the DPD Golkar Party, Kabupaten Magetan. Using the descriptive-qualitative method, this study found the active dynamics of women in the management of the Golkar Party in Kabupaten Magetan , East Java. Although there were various obstacles faced by female cadres in participating, the Golkar Party as a mature organization is ready to educate its female cadres to participate equally with men. Likewise, there is no difference in treatment in providing an opportunity for opinion and position in the activities of the Golkar Party organization in Kabupaten Magetan, East Java. Keywords: Affirmative action, Women's politics, Golkar Party